2020
DOI: 10.1021/acs.orglett.0c01397
|View full text |Cite
|
Sign up to set email alerts
|

SuFEx Activation with Ca(NTf2)2: A Unified Strategy to Access Sulfamides, Sulfamates, and Sulfonamides from S(VI) Fluorides

Abstract: A method to activate sulfamoyl fluorides, fluorosulfates, and sulfonyl fluorides with calcium triflimide and DABCO for SuFEx with amines is described. The reaction was applied to a diverse set of sulfamides, sulfamates, and sulfonamides at room temperature under mild conditions. Additionally, we highlight this transformation to parallel medicinal chemistry to generate a broad array of nitrogen-based S(VI) compounds.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 37 publications
(43 reference statements)
1
55
0
Order By: Relevance
“… 48 They proposed that calcium triflimide coordinates either to the oxygens of the sulfonyl fluoride or the fluorine atom to increase the electrophilicity at sulfur. In 2020, Ball and am Ende 49 ( Scheme 11 b) and Grygorenko 50 ( Scheme 11 c) further extended the use of Ca(NTf 2 ) 2 to other S(VI) fluorides, including sulfamoyl fluorides (R = NR 3 R 4 ), fluorosulfates (R = OAr), and sulfonyl fluorides (R = alkyl or aryl). Notably in the second-generation Ball and am Ende Ca(NTf 2 ) 2 system, the introduction of 1,4-diazabicyclo[2.2.2]octane (DABCO) allowed for room-temperature sulfur-fluoride exchange reactions with amines, even with the significantly more stable sulfamoyl fluorides and fluorosulfates.…”
Section: Catalytic Activation Of S(vi) Fluoridesmentioning
confidence: 99%
“… 48 They proposed that calcium triflimide coordinates either to the oxygens of the sulfonyl fluoride or the fluorine atom to increase the electrophilicity at sulfur. In 2020, Ball and am Ende 49 ( Scheme 11 b) and Grygorenko 50 ( Scheme 11 c) further extended the use of Ca(NTf 2 ) 2 to other S(VI) fluorides, including sulfamoyl fluorides (R = NR 3 R 4 ), fluorosulfates (R = OAr), and sulfonyl fluorides (R = alkyl or aryl). Notably in the second-generation Ball and am Ende Ca(NTf 2 ) 2 system, the introduction of 1,4-diazabicyclo[2.2.2]octane (DABCO) allowed for room-temperature sulfur-fluoride exchange reactions with amines, even with the significantly more stable sulfamoyl fluorides and fluorosulfates.…”
Section: Catalytic Activation Of S(vi) Fluoridesmentioning
confidence: 99%
“… 10 , 23 Overall, it is observed that strong bases and H 2 F – can act as catalysts for the reaction but the exact role is unclear up to now. 10 , 19 , 24 , 25 …”
Section: Introductionmentioning
confidence: 99%
“…[5] After extensive screening of the reaction conditions, we found substitution of the S VI À F with amines could be achieved on water (Table 4). [26,27] The functional group compatibility was excellent on both sides of the substrates, such as the carboxylic acid (9-1), heterocycles (9-2), alcohols (9-2, 9-6), olefins , and the cyano groups (9-10). Aniline (9-6) and hydrazine derivatives (9-9) also afforded the desired ligation with high efficiency.…”
Section: Angewandte Chemiementioning
confidence: 99%